Prevention and Management of Dental Trauma in Primary Teeth in the Context of the COVID-19: A Critical Literature Review - Fernanda Vieira Almeida; Vanessa Polina Pereira da Costa; Helena Silveira Schuch; Marília Leão Goettems (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate and discuss the prevention and management of dental trauma in primary teeth during the COVID-19 pandemic. Material and Methods: Critic literature review, searching electronic databases and Google for articles and guidelines published in English that described prevention and management of dental trauma in primary dentition during the pandemic of COVID-19. Results: 5 publications regarding management and 1 leaflet about prevention for parents were identified. Urgent care is required when the child presents tooth fracture resulting in pain or causing soft tissue trauma and luxation affecting bite. Avulsed teeth should not be replanted and advice and self-help may be sufficient in some situations. Instructions about soft diet and hygiene must be provided. Remote consults are recommended for non-urgent situations and during follow-up to evaluate the presence of sequelae. Aerosol generating procedures should be avoided and, in cases of poor prognosis, extraction is recommended to prevent recurring visits to the dental office. Conclusion: During COVID-19 pandemic, remote consults should be recommended to evaluate traumatic dental injuries in primary dentition. Follow-up should not be neglected and may be performed through remote consultation.